Preferential Reactivity of Dipeptidyl Peptidase-IV Inhibitor-Associated Bullous Pemphigoid Autoantibodies to the Processed Extracellular Domains of BP180 - Mai, Yosuke; Nishie, Wataru; Izumi, Kentaro; Shimizu, Hiroshi (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) is a common autoimmune blistering disease in which autoantibodies target the hemidesmosomal components BP180 and/or BP230 in basal keratinocytes. In BP, 80 to 90% of autoantibodies target the juxtamembranous extracellular non-collagenous 16th A (NC16A) domain of BP180. Recently, the administration of dipeptidyl peptidase-IV inhibitors (DPP4i), which are widely used as antihyperglycemic drugs, has been recognized to be a causative factor for BP. DPP4i-associated BP (DPP4i-BP) autoantibodies tend to target epitopes on non-NC16A regions of BP180, and the pathomechanism for the development of the unique autoantibodies remains unknown. To address the characteristics of DPP4i-BP autoantibodies in detail, we performed epitope analysis of 18 DPP4i-BP autoantibodies targeting the non-NC16A domains of BP180 using various domain-specific as well as plasmin-digested polypeptides derived from recombinant BP180. Firstly, Western blotting showed that only one DPP4i-BP serum reacted with the epitopes on the intracellular domain of BP180, and no sera reacted with the C-terminal domain of the molecule. In addition, only 2 DPP4i-BP sera reacted with BP230 as determined by enzyme-linked immunosorbent assay. Thus, DPP4i-BP autoantibodies were found to mainly target the non-NC16A mid-portion of the extracellular domain of BP. Interestingly, Western blotting using plasmin-digested BP180 as a substrate revealed that all of the DPP4i-BP sera reacted more intensively with the 97-kDa processed extracellular domain of BP180, which is known as the LABD97 autoantigen, than full-length BP180 did. All of the DPP4i-BP autoantibodies targeting the LABD97 autoantigen were IgG1, and IgG4 was observed to react with the molecule in only 7 cases (38.9%). In summary, the present study suggests that IgG1-class autoantibodies targeting epitopes on the processed extracellular domain of BP180, i.e., LABD97, are the major autoantibodies in DPP4i-BP.